C﻿hief digital officers: the state of the art and the road ahead - Lena Kessel; Lorenz Graf-Vlachy (Management Review Quarterly, 2021)
There is a lively debate on chief digital officers (CDOs). Some practitioners stress CDOs' critical role in recrafting digital strategies and accelerating digital transformation, while others predict their disappearance. Academics have also recently begun to study this new executive position and conducted research on CDOs which is, however, scattered across different disciplines and publication outlets. We conduct a systematic literature review that consolidates these initial gains in knowledge. Specifically, we integrate findings on theoretical lenses, research designs, and key themes in studies on CDOs and we propose a framework that organizes CDO research in three broad themes: antecedents of CDO presence, the CDO role, and consequences of CDO presence. We then build on identified gaps to develop an extensive agenda for future research on CDOs. For academic researchers, we not only offer a discipline-spanning overview of knowledge on the topic at hand but also provide useful direction towards fruitful avenues for future research on CDOs. For practitioners, we offer a summary of the current scientific literature on CDOs, including relevant insights on CDO appointments, governance, and performance consequences.
Keywords: M1; M12; M15; 650; Chief digital officer; Systematic literature review; Research agenda; IS Executives; M